Musculoskeletal Disorders and Working Posture among Dental and Oral Health Students - Ng, Andrew (Healthcare (Basel), 2016)
The prevalence of musculoskeletal disorders (MSD) in the dental professions has been well established, and can have detrimental effects on the industry, including lower productivity and early retirement. There is increasing evidence that these problems commence during undergraduate training; however, there are still very few studies that investigate the prevalence of MSD or postural risk in these student groups. Thus, the aim of this study was to determine the prevalence of MSD and conduct postural assessments of students studying oral health and dentistry. A previously validated self-reporting questionnaire measuring MSD prevalence, derived from the Standardised Nordic Questionnaire, was distributed to students. Posture assessments were also conducted using a validated Posture Assessment Instrument. MSD was highly prevalent in all student groups, with 85% reporting MSD in at least one body region. The neck and lower back were the most commonly reported. The final year dental students had the highest percentage with poor posture (68%), while the majority of students from other cohorts had acceptable posture. This study supports the increasing evidence that MSD could be developing in students, before the beginning of a professional career. The prevalence of poor posture further highlights the need to place further emphasis on ergonomic education.